2012
DOI: 10.1159/000336501
|View full text |Cite
|
Sign up to set email alerts
|

Central Prolactin Modulates Insulin Sensitivity and Insulin Secretion in Diabetic Rats

Abstract: Background: Prolactin secretion is self-regulating as it acts upon hypothalamic dopaminergic systems which inhibit prolactin release from the anterior pitutary. Circulating prolactin improves glucose homeostasis by increasing insulin action and secretion, but central prolactin effects on glucose homeostasis have not been examined. Here, we determined that chronic central infusion of prolactin modulates insulin resistance and β-cell function and mass in 90% of pancreatectomized diabetic male rats. Methods: Diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 54 publications
1
34
0
5
Order By: Relevance
“…These mice had reductions in pancreatic islet density and β cell mass, together with blunted insulin secretory responses to glucose compared with wild-type littermates [40]. Physiologically elevated prolactin levels induce normal adaptive processes, including expansion of the β cell mass and improvements in hepatic insulin sensitivity, that ultimately increase glucose-stimulated insulin secretion in diabetic rats [41]. Animal and human studies have clearly shown that the β cell mass influences the insulin secretory capacity and the risk of developing T2DM [42,43]…”
Section: Mechanisms Underlying the Possible Protective Effects Of Brementioning
confidence: 99%
“…These mice had reductions in pancreatic islet density and β cell mass, together with blunted insulin secretory responses to glucose compared with wild-type littermates [40]. Physiologically elevated prolactin levels induce normal adaptive processes, including expansion of the β cell mass and improvements in hepatic insulin sensitivity, that ultimately increase glucose-stimulated insulin secretion in diabetic rats [41]. Animal and human studies have clearly shown that the β cell mass influences the insulin secretory capacity and the risk of developing T2DM [42,43]…”
Section: Mechanisms Underlying the Possible Protective Effects Of Brementioning
confidence: 99%
“…In normal healthy humans, plasma prolactin concentrations peak at night during sleep and are relatively low during the wakeful daylight period of the day (reviewed in [50]), and animal studies indicate this inhibition is due in large part to inhibition from hypothalamic dopaminergic tone [146]. Generally, a large fraction of obese, insulin-resistant humans have diurnal (day-time) plasma prolactin levels that are elevated relative to lean, insulin-sensitive subjects [147][148][149][150][151].…”
Section: Clinical Effects Of Bromocriptine-qr Therapy In the Treatmenmentioning
confidence: 99%
“…The possible explanations for this association were provided by experimental studies showing that mild increases in prolactin levels and placental lactogens during pregnancy determined the increase in beta cell mass and glucose-stimulated insulin secretion [38,39], these modifications being essential to the maintenance of normal glucose metabolism in pregnancy. Moreover, in rats, both intracerebroventricular and intraperitoneal infusions of a low dose of prolactin resulted in a mild increase in circulating prolactin, determining the enhancement of insulin secretion and improvement in insulin sensitivity [40,41]. Indeed, our data showed associations of higher prolactin levels within normal ranges of lower fasting insulin and HOMA-IR values in bivariate analysis.…”
Section: Discussionmentioning
confidence: 49%